Epistolografia jako wyzwanie - Wasąg, Magdalena (Zagadnienia Rodzajów Literackich, 2021)
The article briefly confronts different research perspectives on epistolography. The fundamental Teoria listu (Theory of a Letter) by Stefania Skwarczyńska is indicated as an important reference for many concepts. The category of a beautiful letter proposed by Skwarczyńska is presented by the example of the correspondence between Wisława Szymborska and Kornel Filipowicz — Listy. Najlepiej w życiu ma twój kot (Letters. Your Cat Has the Best in Life). The letters of the future Nobel Prize winner and the master of the storyteller harmoniously combine life and literary elements. They are characterised by irony and humour, which are specific codes of communication. Their form and concepts are evidence of the correspondents’ passionate and strong relationship. The sensitivity to nature shown in them was presented in the context of empathetic imagination. It was linked to both Filipowicz’s biographical experiences and his creative practices, threads that help in the origin of texts such as the short story Krajobraz doskonały (Perfect Landscape) from the volume Śmierć mojego antagonisty (Death of My Antagonist). Nowadays, the need for interdisciplinarity has been pointed out as one of the most important postulates concerning the study of epistolography. The bilateral nature of biography and correspondence continues to be an inspiring issue. The communication paradox of the letter, which is both a dialogue and a monologue, also returns in the investigations of researchers. In the context of the aforementioned studies, the letter continues to fascinate as a phenomenon on the borderline of life and art. For some artists, the letter had a community- creating power. This very meaning was especially emphasised in the perspective of searching for spiritual community, tightening important bonds, lasting and deep friendships based on certain rules. Volumes of correspondence of writers-friends, among others, Julian Tuwim, were cited as an example. The article is an invitation to develop and expand the study of both published correspondence, as well as letters resting in archives in Poland and abroad.